Internet communication through point-to-point protocol on linux operating system - Badjie, Abdoulie F. (2005)
The growth of the internet has meant that different devices are connected together and data has to be exchanged from one place to another. Since the internet consists of many networks connected together using different protocols, there is the need for a single independent protocol which can transport the data from one end to another irrespective of the type of protocol of the origin or destination of the connection. The Point-to-Point Protocol is such a protocol and is designed for simple links which transport packets between two peers. These links provide full-duplex simultaneous bi-directional operation, and are assumed to deliver packets in order. The use of sockets in the internet communication eliminates the reconfiguration of the link between the server and client. It also enables multiple access of a server by many clients. This project demonstrates the processes that’s takes place when accessing a website or doing some client/server computing in the form of a link connecting two computers. The computers communicate through the use of sockets in Point-to-Point Protocol as the Media Access Control in the Data link Layer. Data communication takes place in the form of a Graphic User Interface using text and audio through the two computers.